SIMULATION HEAT AFFECTED ZONE WELDING ON AISI 1045 STEEL USING MATLAB - hardi gunawan; Andi Firdaus; Kontan Tarigan; M Azizi; Deni Shidqi Khaerudini (Universitas Mercu Buana, 2026)
In this Research, AISI 1045 steel plate test objects were welded using SMAW welding. A thermal simulation of the welding process (heat input simulation) is performed by entering the maximum temperature distribution on a 140 x 140 mm plate with a thickness of 4 mm, made of AISI 1045 steel. Initially, the plate has temperature limits of 700 °C, 500 °C, above 1300 °C, and below 0 °C. The bottom of the plate is protected by a constant-temperature shield. The test object is then described numerically using the MATLAB program. In this Research, we can use MATLAB to develop a mathematical and numerical model that captures the effect of the heat-affected zone (HAZ) on the mechanical properties of AISI 1045. This model helps in the understanding of how the heat input provided from the welding process influences the mechanical material properties and allows us to optimize the Influence of the process to obtain the desired results. Calculations carried out using the MATLAB application obtained results in the 9th iteration for errors <1%, namely 0.4681%. Considerable heat input results in low tensile strength; this shows that the welded joint, with the electrodes used and the given welding parameters, produced good joint strength.